Letramentos críticos e o uso da língua alvo no ensino de língua inglesa: um olhar autoetnográfico - Erika Amancio Caetano Soares (2017)
The present study has investigated possible contributions of critical literacies for the use of the target language in English classes at private regular schools in Belo Horizonte. This study aimed at analyzing the possible impact of the critical pedagogical approach in two high school classrooms, by the development and application of critically based activities, so as to observe possible outcomes of such process concerning their language learning as well as their formation as critical and reflexive citizens. The research, qualitatively oriented, counted on an autoethnographic perspective of an action-research performed in two junior high classes at a private regular school in Belo Horizonte. The information generated in this study was co-constructed based on information from me as the participant teacher, my students and a guest participant, through the use of a self-reflexive diary, questionnaires, a focus group of five students and field notes. Given that the current study was constructed over unfinished concepts or definitions open to different nuances and interpretations, a specific perception of the concepts of communicative approach, culture, classroom as culture, crystallization as a methodological approach, autoethnography and action-research (vide glossary) was provided, based on subjective choices within the existing literature, considering the scope of this research. Besides, since the concept of critical literacy has counted on various strings of thought which encompassed both literacies in L1 and L2, the term has assumed a plural form critical literacies. The originality component of this study consisted of understanding the classroom as a community, permeated by inherent cultures and discourses (DIXON; FRANK; GREEN, 1999). In this context, an autoethnographic view of the action-research conducted by me, the researcher, was proposed. Such approach has contributed significantly to strengthen the bonds within my small school community. The autoethnographic perspective represented, along this journey, a more careful look at this intense experience, in which action-research has been adopted as the leading methodology for the generation of the data which gave life to this study. The results have shown that, although critical literacies have been considered a strategy for students engagement and a tool for ELT based on agency and social transformation, as well as a for using the target language as the main means of instruction, it remains necessary for the teacher to create opportunities for students to use the target language in a practical and contextualized way, in environments other than the school settings. Only then will students be provided with chances for autonomous learning and the consequent quest for their ethical, human and citizen education.